Deambulações em torno das Arquitecturas contemporâneas. A construção de um processo de reflexão - Joana Pedrosa de Freitas (2015)
It is based on the idea of architecture as single and unrepeatable action, about a spatial circumstance, that is developed this work. The singularity of the creative process and, at the same time the universality of the primary issues of the architectural act shows how each author starts from a common origin and from there builds his body depending on the choices he makes.We enter in a excursion about the interior worlds of three architects - Lacaton & Vassal, RCR Arquitectes e SANAA - about their origins and their references. In a reverse procedure, we look for a singular work of each group and we recreate its construction process.The more arbitrary and subjective aspects of each architecture are part of the discussion, while we seek identify the structural compositional laws that are common to the entire organization of space.